Improved synthesis of N-Benzylaminoferrocene-based prodrugs and evaluation of their toxicity and antileukemic activity - Daum, Steffen; Sellner, Leopold; Zenz, Thorsten (Journal of medicinal chemistry, 2015)
We report on an improved method of synthesis of N-benzylaminoferrocene-based prodrugs and demonstrate its applicability by preparing nine new aminoferrocenes. Their effect on the viability of selected cancer cells having different p53 status was studied. The obtained data are in agreement with the hypothesis that the toxicity of aminoferrocenes is not dependent upon p53 status. Subsequently the toxicity of a selected prodrug (4) was investigated ex vivo using rat precision cut liver slices and in vivo on hybrid male mice BDF1. In both experiments no toxicity was observed: ex vivo, up to 10 μM; in vivo, up to 6 mg/kg. Finally, prodrug 4 was shown to extend the survival of BDF1 mice carrying L1210 leukemia from 13.7 ± 0.6 days to 17.5 ± 0.7 days when injected daily 6 times at a dose of 26 μg/kg starting from the second day after injection of L1210 cells.
Gesehen am 30.01.2017